DAMPAK ALIH FUNGSI LAHAN TERHADAP STRUKTUR KERUANGAN DI SEWON BANTUL - saherda, agil (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
Land use is related to human activities in certain areas, for example settlements, housing and rice fields. Land use is also land use and the natural environment to meet human needs in carrying out their lives. Development cannot be separated from land use, therefore this study aims to identify land use changes in Sewon District and their impact on spatial planning. The analytical method used is overlay analysis and map interpretation to determine the magnitude of spatial change, and to determine the variables forming the spatial structure. Based on the results of the analysis, it can be seen that there has been a decrease in the use of irrigated rice fields, it can be concluded that the change variables become residential, industrial, housing, trade & services, gardens, vacant land. and green open space. Based on the results of the analysis, Sewon Regency is included in the center of national activities where the transportation network is one of the elements forming the city structure and if it is drawn straight with the spatial concept in the form of an axis, there are four road networks that form a spatial structure, namely Ring Road as Arterial Road, Jalan Parangtritis , Jalan Bantul, Jalan Imogiri Barat as Collectors Street. The four roads above provide high mobility access, and from there facilities are developed to support the activities that occur. This confirms that the road network has a very large influence on the urban spatial structure